The effect of special exercises and assistant apparatus in muscular strength and some mechanical variables of upper limbs for bodybuilding’s’ players - et. al., Karrar Ibrahim Hussein, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Current research aimed to study the variances in muscle strengths in the body and to see the extent of its impact on the evolution of muscle strength and muscle size in terms of its circumference and depth. This research’s sample included players from the province of Babylon in body building sports and numbered five players by one experimental group with tribal and dimensional test. Researchers used the experimental method by implementing several exercises and devices designed for the purpose of developing muscle strength and increasing the muscle balance of the upper limbs by reducing the differences on both sides of the body that lasted eight weeks by four training units during the week. Researchers concluded that the exercises used, and the device designed to have a positive effect in the development of muscle strength in the sample of research .